Advancements in Analytical Techniques for Water Source ContaminationAnalysis in Forensics: A Comprehensive Review - Ankit Singh; Animesh Pandey; Gunjan Saxena (Indian Journal of Forensic Medicine and Pathology, 2025)
An essential aspect of forensic science is the analysis of water source pollution, which offers vital insights into crimes against the environment, health-related occurrences, and the recognition of those responsible. Contamination of water sources is a major problem for forensic investigations, requiring sophisticated analytical methods for precise and prompt identi𿿿cation of pollutants. Thisreview presents a variety of cutting-edge techniques, tools, and interdisciplinary approaches that have greatly improved the accuracy, sensitivity, and effectiveness of water analysis. The use of remote sensing technologies and the dif𿿿cultiesin applying them to forensic water analysis are given particular attention. It explores developments in chromatographic methods, such as liquid and gas chromatography (GC and LC), and explains their application and contribution to the evaluation of water quality. After that, there is a focus on sensor technologies, explaining how new real-time monitoring sensors such as electrochemical, optical, and nano sensors have emerged and how they are used in forensic settings. The review concludes by outlining the challenges of applying advanced techniques to forensic water analysis and identi𿿿es key areas for future research, underscoringthe need for continued methodological innovation. This thorough investigation seeks to promote improvements in the watery𿿿eld source pollution nalysis by erving as a useful resource for scholars, forensic scientists, and legislators.